2006
DOI: 10.1038/nrg1879
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of phosphatidylinositol 3-kinases as regulators of growth and metabolism

Abstract: Phosphatidylinositol 3-kinases (PI3Ks) evolved from a single enzyme that regulates vesicle trafficking in unicellular eukaryotes into a family of enzymes that regulate cellular metabolism and growth in multicellular organisms. In this review, we examine how the PI3K pathway has evolved to control these fundamental processes, and how this pathway is in turn regulated by intricate feedback and crosstalk mechanisms. In light of the recent advances in our understanding of the function of PI3Ks in the pathogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
2,671
2
43

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,906 publications
(2,735 citation statements)
references
References 153 publications
19
2,671
2
43
Order By: Relevance
“…It has been shown that p110b possesses both lipid and protein kinase activities (reviewed in Bader et al, 2005;Engelman et al, 2006). To determine which activity of p110b kinase is involved in AR transactivation, we tested the effect of different p110b mutants, a total kinase-dead mutant (K805R) and a protein kinase only mutant (PKO, lipid kinase deficient) on Figure 1 Phosphoinositide 3-OH kinases (PI3K) p85a and p110b isoforms are essential for androgen-induced androgen receptor (AR) transactivation and cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that p110b possesses both lipid and protein kinase activities (reviewed in Bader et al, 2005;Engelman et al, 2006). To determine which activity of p110b kinase is involved in AR transactivation, we tested the effect of different p110b mutants, a total kinase-dead mutant (K805R) and a protein kinase only mutant (PKO, lipid kinase deficient) on Figure 1 Phosphoinositide 3-OH kinases (PI3K) p85a and p110b isoforms are essential for androgen-induced androgen receptor (AR) transactivation and cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Because of their important roles in cell signaling, elevated activities of PI3K pathway due to PTEN inactive mutation has long been considered as a key player in cancer pathogenesis including prostate cancers (Li et al, 1997;Steck et al, 1997;Murillo et al, 2001; reviewed in Engelman et al, 2006). However, no information is currently available about the genetic phenotype and expression pattern of PI3K isoforms in human prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many known oncogenes, such as mutated ERBB, insulin-like growth factor-1 (IGF1), c-Kit (stem-cell factor receptor), overexpressed chemokine receptors, mutated Ras, BCR-ABL and elevated levels of the proto-oncogene Src, to name but a few, provide constitutive input signals to PI3K 6,30 . The finding that the 3-lipid phosphatase PTEN (phosphatase and tensin homologue deleted on chromosome ten) is frequently mutated in numerous late-stage tumours finally demonstrated that elevated levels of PtdIns(3,4,5)P 3 contribute to oncogenesis 31,32 .…”
Section: Dysregulated Lipid Signalling In Cancermentioning
confidence: 99%